Peranan Kantor Urusan Agama Dalam Mengantisipasi Pernikahan Usia Dini: Studi Kasus Kecamatan Citeureup Kabupaten Bogor - Muhammad Julian; Suyud Arief; Ahmad Mulyadi Kosim (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
This study examines the role of the Office of Religious Affairs (KUA) in Citeureup District, Bogor Regency in anticipating early marriage. In more detail, the problem is the number of early marriages in the Citeureup District, Bogor Regency, which is caused by certain factors. This study aims to analyze how the role of KUA in Citeureup District in anticipating early marriage. This research is a research that uses qualitative methods with the type of research used by the author is juridical and normative Islamic law. The results of this study are that the role of KUA in Citeureup District in anticipating early marriage has been running effectively. The KUA of Citeureup District has succeeded in minimizing the number of age marriages by conducting regular guidance and counseling efforts that make the public understand the influence of early marriage. Then the influence of the KUA in Citeureup District in minimizing the number of early marriages is very large. This can be seen through the data that from 2020 to 2021 it has decreased. Thus, the KUA of Citeureup District is very influential in efforts to minimize the number of early marriages, especially in the Citeureup District..